2008
DOI: 10.1292/jvms.70.887
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Architecture of the Rabbit Eye: A Scanning Electron Microscopic Study of Vascular Corrosion Casts

Abstract: ABSTRACT. The microvasculature of the eyes of 5 rabbits was investigated using scanning electron microscopy on corrosion casts. The study revealed that the pars plana vessels draining blood from the iris and ciliary body coursed directly into the anterior vortex venous system constituting the scleral venous plexus (the venous circle of Hovius). The episcleral vasculature was found to possess a specialized morphology, with channels draining the aqueous humor. The capillaries of the third palpebral, bulbar and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…The presence of gradients in apparently random locations may correlate with feeding vessels that merge from below the plane of the image and are not visible. Anatomical studies have demonstrated deep penetrating vessels within the thick nerve fiber layer of the rabbit [34]–[38]. The intravascular gradients may be a reflection of variations in local metabolic activity and represent a novel method of studying microvascular oxygen transport completely non-invasively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of gradients in apparently random locations may correlate with feeding vessels that merge from below the plane of the image and are not visible. Anatomical studies have demonstrated deep penetrating vessels within the thick nerve fiber layer of the rabbit [34]–[38]. The intravascular gradients may be a reflection of variations in local metabolic activity and represent a novel method of studying microvascular oxygen transport completely non-invasively.…”
Section: Discussionmentioning
confidence: 99%
“…This physiology provides an excellent animal model to calibrate our spectral measurements over a wide range of in vivo hemoglobin oxygen saturation. In addition, the well described anatomy of retinal vessels provides an ideal imaging target in vivo [34]–[38]. Specifically, the largest retinal vessels (100–200 micron diameter) in rabbits lay on top of a non-pigmented nerve fiber layer (Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…However, the measurements of blood flow velocities in other orbital blood vessels were much more difficult in the rabbits using the CDI technique 7 . The tortuous orientations and variable sizes of short and long posterior ciliary arteries in rabbits complicated their identifications 24,25 . In this study, we found that it was difficult to visualize the posterior ciliary arteries as well as the small central retinal artery in the rabbits with the 17–5 MHz automatic frequency adjusting ultrasound transducer.…”
Section: Discussionmentioning
confidence: 73%
“…The anatomy of the rabbit retina has been described extensively in previous work. [33]–[36] The vascular distribution within the rabbit retina is localized (to the medullary rays) and corresponding arteries and veins are easily imaged with conventional fundus photography. Previous studies from our lab have demonstrated that argon laser photothrombosis can induce retinal vein occlusion (RVO) and the commonly observed clinical sequelae including intraretinal hemorrhages, leakage, capillary non-perfusion, and collateral circulation.…”
Section: Methodsmentioning
confidence: 99%